Spyglass percutaneous transhepatic lithotripsy of symptomatic recurrent lithiasis of the intrahepatic bile duct with distal stenosis - Colombi, Davide; Bodini, Flavio Cesare; Morelli, Nicola; Aragona, Giovanni; Ciatti, Corrado; Maniscalco, Pietro; Michieletti, Emanuele (Acta Biomedica Atenei Parmensis, 2022)
In patients with symptomatic intrahepatic biliary lithiasis, the treatment is usually discussed by a multidisciplinary team. Although hepatectomy is considered as definitive treatment, when lobar atrophy is absent, endoscopic procedures are frequently proposed as first-line treatment due the low invasiveness and for sparing liver parenchyma. Percutaneous route is used in case of peroral approach failure. We present a case of recurrent symptomatic intrahepatic biliary lithiasis of the right posterior hepatic duct, sustained by downstream biliary stenosis. Peroral cholangioscopy failed to visualize the stone for the accompanying stenosis. Thus, the patient was successfully treated with percutaneous transhepatic lithotripsy performed with Spyglass direct visualization system II (Boston Scientific Inc., Natick, Massachusetts, USA). During the procedure, the biopsy of the biliary stenosis revealed fibrosis, which was treated by cholangioplasty with cutting balloon. After 15 months, the patient is asymptomatic, with moderate residual stenosis in absence of calculi at follow-up magnetic resonance cholangiography.